Survival patterns in teenagers and young adults with cancer in the United Kingdom: Comparisons with younger and older age groups. Issue 17 (November 2015) - Stark, Dan; Bowen, David; Dunwoodie, Elaine; Feltbower, Richard; Johnson, Rod; Moran, Anthony; Stiller, Charles; O'Hara, Catherine
Highlights: Six survival patterns observed when comparing TYA survival to children and adults. Survival estimates based on high quality UK cancer registry data. TYA 5-year survival better than both adults and children in CNS tumours. TYA 5-year survival poorer than both adults and children in bone tumours and STS. Necessity to address age-specific determinants of cancer survival in future studies. Abstract: Aims: We aimed to describe and compare survival in teenagers and young adults (TYAs) with cancer to that of younger children and older adults, to identify sub-populations at greater or lesser risk of death. Methods: We compared survival in cancer patients diagnosed in the United Kingdom aged 13–24 years (TYAs) to those aged 0–12 (children) and 25–49 years (adults) using the National Cancer Data Repository. All cases had a first cancer diagnosis between 1st January 2001 and 31st December 2005 with censor date 31st December 2010 or death if earlier. Results: We found six distinct statistically significant survival patterns. In pattern 1, the younger the age-group the better the 1- and 5-year survival (acute lymphoid leukaemia, carcinoma of ovary and melanoma). In pattern 2, TYAs had a worse 5-year survival than both children and young adults (bone and soft tissues sarcomas). In pattern 3, TYAs had a worse 1-year survival but no difference at 5-years (carcinoma of cervix and female breast). In pattern 4, TYAs had better 1-year survival than adults, but no difference at 5 years (carcinoma of liver and intrahepatic bile ducts, germ cell tumours of extra-gonadal sites). In pattern 5, the younger the age-group the better the 5-year survival, but the difference developed after 1-year (acute myeloid leukaemia, carcinoma of colon and rectum). In pattern 6, there was no difference in 1- and 5-year survival between TYAs and adults (testicular germ cell tumours, ovarian germ cell tumours and carcinoma of thyroid). Conclusion: TYAs with specific cancer diagnoses can be grouped according to 1- and 5-year survival patterns compared to children and young adults. To further improve survival for TYAs, age-specific biology, pharmacology, proteomics, genomics, clinician and patient behaviour studies embedded within clinical trials are required.